Log income versus linear income: an application of the encompassing principle - Ermini, L; Hendry, D (Nuffield College (University of Oxford), 1995)
An open question in empirical economics is whether models should be estimated by using the logarithm of the relevant economic variables or their actual, or "linear", values. This paper applies the principle fo encompassing to suggest specification and mis-specification tests of log versus linear individudal equations fitted to l(1) data, and illustrates tje analysis for US quarterly disposable income. The finite-sample properties of the encompassing tests are examined in a Monte Carlo experiment customized to the parameter values in the empirical analysis.